Effect of gear design on catch damage on cod (Gadus morhua) in the Barents Sea demersal trawl fishery - Brinkhof, Jesse; Herrmann, Bent; Sistiaga, Manu; Larsen, Roger B.; Jacques, Nadine; Gjøsund, Svein Helge (Food Control, 2020)
Damage incurred during the catch process is an indicator of the overall quality of fish and fish welfare. Because catch quality is difficult to improve once it has deteriorated, it is important to preserve quality during the catch process. Atlantic cod ( Gadus morhua ) is the most important species in the Barents Sea bottom trawl fishery. Bottom trawling is a non-benign fishing method, and it is therefore considered important to reduce damage imparted to fish during capture, and subsequently improve catch quality and fish welfare. In the present study, the levels of damage on cod captured with a new gear design were assessed in the Barents Sea bottom trawl fishery. Furthermore, this study investigated to what extent the compulsory sorting grid and diamond mesh codend configuration employed in the fishery is responsible for the damage incurred by cod during the capture process. In total, 750 cod captured over 25 hauls were evaluated for catch damage (marks, ecchymosis, exsanguination, and scale loss). The results showed that substituting the grid and codend configuration with a four-panel selective knotless section followed by a gentle codend increased the probability of cod having no catch damage by 6.00% (CI: 0.6%–11.41%). Moreover, the gentle codend led to a significant reduction in the severity of all catch damage categories.